Rare Abdominal Desmoid Tumor: Case Report and Review of Literature - Gracjan Sitarek; Marta Żerek; Wojciech Płonka; Damian Chruścicki; Paulina Bednarczyk; Marcin Pelc (Nicolaus Copernicus University in Toruń, 2024)
A desmoid tumor is a clonal fibroblast proliferation, occurring in deep soft tissues with a significant recurrence tendency. Aggressive fibromatosis is a rare disease. The prevalence in the population ranges from 2 to 4 cases per million. Mentioned neoplasms are highly unpredictable in terms of development. Typically, in the course of desmoid tumors, metastases do not occur, but they often infiltrate the surrounding tissues, which may be associated with numerous complications. There are currently no randomized standards of therapy designated, which is undoubtedly a challenge when referring to treatment. To a 37 year old patient, due to a pathological mass in the abdomen, the MR examination was performed. It showed the presence of an irregular, heterogeneous structure on the right side of the abdominal cavity. A laparotomy was performed. During the procedure adhesions were released and the giant abdominal tumor was removed in one block with part of the duodenum, caecum, ascending colon and part of ileum. End-to-end duodenal anastomosis and stapled, side-to-side ileo-transverse anastomosis were used. The surgical field was being drained. The postoperative course was uneventful. Tissue material was collected for a routine, histopathological examination in which the intra-abdominal form of fibromatosis was diagnosed. The macroscopic image describes a tumor with dimensions of 25.0 cm x 25.0 cm x 20.0 cm.